Service Quality: A Key Determinant of Organisational Competitiveness - Njovo, Munodawafa; Makacha, Caroliny (Archives of Business Research, 2015)
The study attempts to establish the link between service quality and competitiveness. Organisations have largely been focusing on making attempts to satisfy customer by focusing on pricing and distribution strategies. Service quality has often been neglected and this has often resulted in depressed organisational performance. A pre-dominantly descriptive research design was used. Questionnaires were distributed among respondents in organisations that are in the ICT service and distribution business. The respondents comprised of employees and customers of the said organisations. A sample size of 44 was used. It was concluded that service quality was instrumental in facilitating multiple advantages which put companies in good stead to fight competition